Quantitative Analysis of Watershed Geomorphology Using Remote Sensing Techniques - Singh, Surendra (Annals of Arid Zone, 2016)
Dimensional and dimensionless geomorphic characteristics/variables of 13 watersheds of the Jojri catchment have been discussed in this paper, using remote sensing techniques and ground truth. Interrelationship between these geomorphic variables have also been established and these are, by and large, significantly correlated to each other. Based on these findings, priorities have been fixed under four calegories for the development of watersheds into croplands, grasslands, woodlands and water harvesting at suitable sites.